FAKTOR - FAKTOR YANG MEMPENGARUHI JUMLAH PEMBELIAN TELUR AYAM RAS DI PASAR TERONG, KOTA MAKASSAR - Muhammad Arif; Syahriadi Kadir; Agustina Abdullah (State Islamic University (UIN) Alauddin, 2014)
ABSTRACT. Research has been conducted to determine the Factors Affecting Purchase Amount at Market Broiler Eggs Eggplant, Makassar. Held on August 10, 2013 until the date of 12 September 2013 in the Market Eggplant, Makassar. This research is a kind of explanatory Quantitative Study is the type of research that look at the effect of one variable with another variable and to test hypotheses and data sources used are primary data and secondary data, then using multiple linear regression method. The results obtained show that the price, quality of eggs, quality of service, revenue, and number of family members simultaneously significant effect on the amount of purchase eggs, but in partial service quality does not significantly influence the amount of the purchase eggs at the Market Eggplant, Makassar City.